An Update on the Evolution of Glucosyltransferase (Gtf) Genes in Streptococcus - Xu, Rong-Rong; Yang, Wei-Dong; Niu, Ke-Xin; Wang, Bin; Wang, Wen-Mei (Frontiers in Microbiology, 2018)
In many caries-promoting Streptococcus species, glucosyltransferases (Gtfs) are recognized as key enzymes contributing to the modification of biofilm structures, disruption of homeostasis of healthy microbiota community and induction of caries development. It is therefore of great interest to investigate how Gtf genes have evolved in Streptococcus. In this study, we conducted a comprehensive survey of Gtf genes among 872 streptococci genomes of 37 species and identified Gtf genes from 364 genomes of 18 species. To clarify the relationships of these Gtf genes, 45 representative sequences were used for phylogenic analysis, which revealed two clear clades. Clade I included 12 Gtf genes from nine caries-promoting species of the Mutans and Downei groups, which produce enzymes known to synthesize sticky, water-insoluble glucans (WIG) that are critical for modifying biofilm structures. Clade II primarily contained Gtf genes responsible for synthesizing water-soluble glucans (WSG) from all 18 species, and this clade further diverged into three subclades (IIA, IIB, and IIC). An analysis of 16 pairs of duplicated Gtf genes revealed high divergence levels at the C-terminal repeat regions, with ratios of the nonsynonymous substitution rate (dN) to synonymous substitution rate (dS) ranging from 0.60 to 1.03, indicating an overall relaxed constraint in this region. However, among the clade I Gtf genes, some individual repeat units possessed strong functional constraints by the same criterion. Structural variations in the repeat regions were also observed, with detection of deletions or recent duplications of individual repeat units. Overall, by establishing an updated phylogeny and further elucidating their evolutionary patterns, this work enabled us to gain a greater understanding of the origination and divergence of Gtf genes in Streptococcus.